Developing virtue and rehabilitating vice: Worries about self-cultivation and self-reform. Issue 2 (2nd April 2016) - Battaly, Heather
Abstract: Aristotelian virtue theorists have emphasized the role of the self in developing virtue and in rehabilitating vice. But this article argues that, as Aristotelians, we have placed too much emphasis on self-cultivation and self-reform. Self-cultivation is not required for developing virtue or vice. Nor will sophia -inspired self-reform jumpstart change in the vicious person. In each case, the external environment has an important role to play. One can unwittingly acquire virtues or vices from one's environment. Likewise, a well-designed environment may be the key ingredient for jumpstarting change in the vicious person. Self-cultivation and late-stage self-reform are not ruled out, but the role of the self in character development and rehabilitation is not as exalted as we might have thought.